2021
DOI: 10.14453/aabfj.v15i2.7
|View full text |Cite
|
Sign up to set email alerts
|

Australian, Malaysian and Indonesian Accounting Academics' Teaching Experiences During the COVID-19 Pandemic

Abstract: This study analyses and presents accounting academics' experiences in six universities in Australia, Malaysia, and Indonesia to adapt to the swift change to the remote virtual classroom delivery model forced by the COVID-19 pandemic, while also gaining valuable lessons from this unique situation. In this study, autoethnography's basic principles were used. The main results suggest that the universities' combined current information and communication technologies, learning management systems, blended learning e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 14 publications
2
15
0
3
Order By: Relevance
“…Consistent with within-country studies, a few comparative studies have shown that the pandemic impacted higher education students in their financial situations, technological access, overall quality and satisfaction of instruction, as well as their overall wellbeing (Djajadikerta et al, 2021;Ma et al, 2021;Mlambo and Ndebele, 2021;Tejegor et al, 2020;Tang et al, 2021). A comparative study involving 62 countries from Aristovnik et al (2020) has also shown similar adverse effects on students' performance.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Consistent with within-country studies, a few comparative studies have shown that the pandemic impacted higher education students in their financial situations, technological access, overall quality and satisfaction of instruction, as well as their overall wellbeing (Djajadikerta et al, 2021;Ma et al, 2021;Mlambo and Ndebele, 2021;Tejegor et al, 2020;Tang et al, 2021). A comparative study involving 62 countries from Aristovnik et al (2020) has also shown similar adverse effects on students' performance.…”
Section: Introductionmentioning
confidence: 81%
“…We decided to focus on these four domains of questions for several reasons. First, comparative studies around the impact of the COVID-19 pandemic have shown that higher education students across the world are negatively impacted in these four domains (Djajadikerta et al, 2021;Ma et al, 2021;Mlambo and Ndebele, 2021;Tejegor et al, 2020;Tang et al, 2021;Aristovnik et al, 2020). Second, before the COVID-19 pandemic, studies centered on firstgeneration, low-income, and rural higher education students showed that these subgroups of students faced barriers to navigating their education in their respective higher education systems, including limited access to technology as well as higher financial and mental distress (Bastedo & Jaquette, 2011;Byun et al, 2012;Engle & Tinto, 2008;Eagle & Tinto;2008;House et al, 2020;Irvin et al, 2012;Kilgo et al, 2018;Lightweis, 2014;Padron, 1992;Tate et al;2015).…”
Section: Data and Samplementioning
confidence: 99%
“…The student is not the sole stakeholder in education; both academicians and administrative personnel are deeply integrated into the educational ecosystem. Therefore there are three research articles, including Djajadikerta et al (2021), Bokolo et al (2020), Nagaletchimee (2019), that evaluated how institutional, mainly the staff contribute to the effectiveness of blended learning. The study of Nagaletchimee ( 2019) used a qualitative case study to identify the challenges faced by fifteen lecturers who were familiar with blended learning when they wanted to make a change from the traditional classroom.…”
Section: Participantsmentioning
confidence: 99%
“…The author developed a model for evaluating institutional readiness on blended learning. More recently, Djajadikerta et al (2021) noted that without compliance technologies support from the university, such as establishing of a learning management system.…”
Section: Participantsmentioning
confidence: 99%
“…The current business environment, which is dominated by rapid technological developments and fierce business competition, requires every organization to continue to learn and adapt (Djajadikerta et al , 2021; Ong and Djajadikerta, 2019). Acquisition of relevant and up-to-date knowledge has become necessary for both the organization and its staff to maintain competitiveness and, if possible, growth (Lange et al , 2000).…”
Section: Background Setting and Proposition Developmentmentioning
confidence: 99%